Implementasi Konsep “Studio Tour” pada Sentra UKM-Jahit (Disperindag) di Bukit Barisan Surabaya - Benita Antonia Gunawan; Mariana Wibowo (Intra, 2019)
Surabaya has provided a place for community activities. But some of the places are less adequate or less attractive, so that Surabaya residents rarely or unwillingly come. For the SME Sewing Center, the government has provided a place but not being used maximally. The problem is that there are not many visitors that comes, the training site that have being used optimally, and not comfortable. Re-designing the space by giving it facility and maximizing rooms function with the needed room and meet the requirement.Design by providing facilities and maximizing the function of space with the space needed and meeting needs. So it can attract visitors and the tailors profit can increase. This design used design thinking methods, and that is understand, observation, point of view, ideate, prototype, and test. The results obtained could enhance and develop these SME center with an educational and historical approach about sewing. Facilities that is designed are, mini gallery, souvenir area, café and fashion catwalk area